Biological activity of neosergeolide and isobrucein B (and two semi-synthetic derivatives) isolated from the Amazonian medicinal plant Picrolemma sprucei (Simaroubaceae) - Silva, Ellen CC; Cavalcanti, Bruno C; Amorim, Rodrigo CN; Lucena, Jorcilene F; Quadros, Dulcimar S; Tadei, Wanderli P; Montenegro, Raquel C; Costa-Lotufo, Letícia V; Pessoa, Cláudia; Moraes, Manoel O; Nunomura, Rita CS; Nunomura, Sergio M; et al. (Memórias do Instituto Oswaldo Cruz, 2009)
In the present study, in vitro techniques were used to investigate a range of biological activities of known natural quassinoids isobrucein B (1) and neosergeolide (2), known semi-synthetic derivative 1,12-diacetylisobrucein B (3), and a new semi-synthetic derivative, 12-acetylneosergeolide (4). These compounds were evaluated for general toxicity toward the brine shrimp species Artemia franciscana, cytotoxicity toward human tumour cells, larvicidal activity toward the dengue fever mosquito vector Aedes aegypti , haemolytic activity in mouse erythrocytes and antimalarial activity against the human malaria parasite Plasmodium falciparum . Compounds 1 and 2 exhibited the greatest cytotoxicity against all the tumor cells tested (IC50 = 5-27 µg/L) and against multidrug-resistant P. falciparum K1 strain (IC50 = 1.0-4.0 g/L) and 3 was only cytotoxic toward the leukaemia HL-60 strain (IC50 = 11.8 µg/L). Quassinoids 1 and 2 (LC50 = 3.2-4.4 mg/L) displayed greater lethality than derivative 4 (LC50 = 75.0 mg/L) toward A. aegypti larvae, while derivative 3 was inactive. These results suggest a novel application for these natural quassinoids as larvicides. The toxicity toward A. franciscana could be correlated with the activity in several biological models, a finding that is in agreement with the literature. Importantly, none of the studied compounds exhibited in vitro haemolytic activity, suggesting specificity of the observed cytotoxic effects. This study reveals the biological potential of quassinoids 1 and 2 and to a lesser extent their semi-synthetic derivatives for their in vitro antimalarial and cytotoxic activities.